Use of artificial intelligence from an ethical perspective in agronomy: Global, national (Cuba) and local (Trinidad) analysis - Delvis Valdés Zayas; Rogelio Pérez Rojas (Social Agriculture, Food System, and Environmental Sustainability, 2026)
Background: Artificial intelligence (AI) is emerging as a transformative tool in global agriculture, although its integration entails ethical implications that may exacerbate inequalities. This research provides a critical analysis of the ethical use of AI in agronomy, examining global, national (Cuba) and local (Trinidad) contexts. Methods: The study employed mixed methodology with systematic review, surveys (n=120), focus groups (n=25) and key informant interviews. Quantitative data were analyzed through descriptive and inferential statistics, while qualitative data underwent thematic analysis. Findings were integrated through a SWOT analysis and validated using methodological triangulation. Findings: Results reveal a significant digital divide (only 10% of farmers in Trinidad report acceptable connectivity) and high interest (70%) in contextualized solutions. This research identify that 78% of technicians express concern about algorithmic biases in solutions not adapted to the Cuban context. Based on SWOT analysis, we propose a four-dimensional action plan with axes on infrastructure, training, contextualized development and governance. Conclusion: The study concludes that ethical AI implementation in Cuban agriculture requires a sovereign approach prioritizing frugal solutions, community governance and alignment with the socialist production model. Novelty/Originality of this article: The uniqueness of this research lies in its critical ethical assessment of the integration of artificial intelligence (AI) within a non-Western agricultural framework, specifically by comparing the global discourse on AI with local realities in Cuba and Trinidad.